Tożsamość jako zadanie – narracja emancypacyjna - Leppert, Roman (Studia Edukacyjne, 2018)
At the basis of the distinguished narrative regarding identity as a task there is the emancipatory interest, distinguished by J. Habermas, constitutive for cognition. Referring to the results of the study on the psychosocial condition of the youth, the author formulates a hypothesis which claims that in the case of the studied group, we are dealing with a generation of potential frustrates (or the deficitof existential rebellion).